Reactive oxygen species-responsive theranostic nanoparticles for enhanced hypoxic tumor photodynamic therapy via synchronous HIF-1α inhibition and ATP depletion. (1st July 2019) - Zhao, Caiyan; Li, Yunhao; Shao, Leihou; Wang, Xuan; Lu, Jianqin; Li, Xianlei; Chen, Long; Cui, Xinyue; Sheng, Wang; Deng, Xiongwei; Wu, Yan
Abstract : ROS-responsive nanoparticles were designed to co-deliver the small molecule HIF-1α inhibitor Doxy and the photosensitizer IR780 for enhanced PDT efficiency. Abstract : A major impediment in photodynamic therapy (PDT) against hypoxic tumors is that the O2 -dependent PDT is seriously limited by the intrinsic hypoxic feature. Hypoxia-inducible factor-1 alpha (HIF-1α) is a key transcription factor in tumor development and especially accumulates in hypoxic tumors and has been recognized as a novel therapeutic target. Herein, we developed small molecule HIF-1α inhibitor Doxy and IR780 photosensitizer co-incorporated methoxy poly(ethylene glycol)- b -poly-(propylene sulfide) (mPEG50 - b -PPS45 ) nanoparticles (NPs/ID) as an ROS-responsive theranostic system designed to enhance PDT efficiency by combining the benefits of anti-HIF-1α therapy and ATP depletion. NPs/ID with reinforced phototherapy response in hypoxic tumors displayed enhanced photocytotoxicity compared to NPs/I that only exhibited the PDT effect. On the other hand, NPs/ID have the capacity to reduce the supply of intracellular ATP and destabilize the intracellular redox homeostasis for enough ROS generation by suppressing the HIF-1α expression, thereby facilitating the therapeutic efficiency of PDT. Significantly, NPs/ID displayed effective tumor targeting and NIR imaging ability and an improved in vivo efficacy in a xenograft MDA-MB-231 mouse tumor model compared with bare PDT. These findings demonstrate that the ROS-responsive theranostic NPs/ID with special anti-HIF-1α and ATP depletion behavior represent an attractive approach for overcoming the problems of PDT in hypoxic tumors.